(untitled) (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2021)
The materialization of the contactless transmission is achieved in theory and practice through different contactless coupling circuits, generically called "contactless couplers". In this paper, we analyze by the finite element method, in 2D approximation, the electric field produced by an inductive coupler in various simplified construction variants and calculate specifically related quantities of practical importance such as electric field distribution in the field of calculation, the electric field strength in the vicinity of the inductive coupler, equipotential lines, reactive power, equivalent capacities, etc.